Monitoring biosecurity in poultry production: an overview of databases reporting biosecurity compliance from seven European countries - Delpont, Mattias; Salazar, Luis G.; Dewulf, Jeroen; Zbikowski, Artur; Szeleszczuk, Piotr; Dufay-Lefort, Anne-Christine; Rousset, Nathalie; Spaans, Annick; Amalraj, Arthi; Tilli, Giuditta; Piccirillo, Alessandra; Devesa, Aitor; et al. (Frontiers in Veterinary Science, 2023)
Compliance with required on-farm biosecurity practices reduces the risk of contamination and spread of zoonotic and economically important diseases. With repeating avian influenza epidemics in the poultry industry, the need to monitor and improve the overall level of biosecurity is increasing. In practice, biosecurity compliance is assessed by various actors (e.g., academic, private and public 2 This is a provisional file, not the final typeset article institutions), and the results of such assessments may be recorded and gathered in databases which are seldom shared or thoroughly analyzed.This study aimed to provide an inventory of databases related to the assessment of biosecurity in poultry farms in seven major poultry-producing European countries to highlight challenges and opportunities associated with biosecurity data collection, sharing and use.The institutions in charge of these databases were contacted and interviewed using a structured questionnaire to gather information on the main characteristics of the databases and the context of their implementation.A total of 20 databases were identified, covering the gamut of poultry species and production types. Most databases were linked to veterinary health authorities or academia, and to a lesser extent interbranch organizations. Depending on the institutions in charge, the databases serve various purposes, from providing advice to enforcing regulations. The quality of the biosecurity data collected is believed to be quite reliable, as biosecurity is mostly assessed by trained farm advisors or official veterinarians and during a farm visit. Some of the databases are difficult to analyze and/or do not offer information concerning which biosecurity measures are most or least respected. Moreover, some key biosecurity practices are sometimes absent from certain databases. Although the databases serve a variety of purposes and cover different production types, each with specific biosecurity features, their analysis should help to improve the surveillance of biosecurity in the poultry sector and provide evidence on the benefits of biosecurity.